RANCANG BANGUN SISTEM PEMANTAUAN KUALITAS UDARA BERBASIS ARDUINO UNTUK MENDETEKSI POLUSI UDARA DI PERKOTAAN - Nugroho, Yusuf Cahyo; Mahardiko, Alief Arifin; Dhelia, Shafira Salma; Nuraini, Afifah; Harsadi, Paulus (STMIK Sinar Nusantara, 2023)
Air pollution is a pressing environmental issue that poses significant risks to human health and the environment. To address this issue, the development of a reliable air quality monitoring system is essential. This research focuses on the design and implementation of a monitoring system based on Arduino Uno microcontroller and sensors such as MQ135, MQ136, and DHT11. The system aims to detect and measure air pollutants, temperature, and humidity levels. The Arduino Uno processes the data collected from the sensors and displays the information on the LCD screen. The system provides real-time monitoring of air quality, allowing quick action to be taken to improve the environment. The use of an Arduino Uno microcontroller enables efficient data processing and control of the overall system operation. The MQ135 sensor is used to detect and measure levels of air pollutants, particularly carbon monoxide (CO). The MQ136 sensor, on the other hand, is used to detect and measure levels of certain air pollutants, such as sulfur dioxide (SO2). In addition, the DHT11 sensor is used to measure the temperature and humidity levels in the air. The results of testing carried out 16 times under the condition of good conditions resulted in an average of CO 8.6 and SO2 15,25 where it is included in the high accuracy category.